1997
DOI: 10.1002/j.1552-4604.1997.tb04302.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxaprozin and Piroxicam, Nonsteroidal Antiinflammatory Drugs with Long Half‐Lives: Effect of Protein‐Binding Differences on Steady‐State Pharmacokinetics

Abstract: The nonsteroidal antiinflammatory drugs (NSAIDs) oxaprozin and piroxicam have long elimination half-lives (t 1/2 approximately 55 hours), permitting once-daily dose regimens. The protein-binding characteristics of these drugs, however, vary widely. This study examines the effect of these binding differences on the drugs' disposition kinetics at steady state. A total of 52 participants (26 young healthy volunteers, and 26 elderly osteoarthritic patients, 15 men and 37 women (2 of them poor metabolizers of debri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…According to previous studies, piroxicam, just like ranitidine, is known as a drug with EHC (27-31, 14, 32). Figures 2 and 3 however confirm that ranitidine does not have similar long elimination time in humans as stated for piroxicam (23,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 56%
“…According to previous studies, piroxicam, just like ranitidine, is known as a drug with EHC (27-31, 14, 32). Figures 2 and 3 however confirm that ranitidine does not have similar long elimination time in humans as stated for piroxicam (23,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 56%
“…In human, CYP enzyme activity studies showed higher clearance in males for CYP1A2-(Caucasian population only) (Shimada et al, 1994) and CYP2E1-associated substrates (Sato et al, 1975;Chen et al, 2002;Franconi et al, 2007), whereas CYP3A4- (Austin et al, 1980;Kahan et al, 1986;Hulst et al, 1994;Dilger et al, 1999;Krecic-Shepard et al, 2000) and CYP2B6-associated (Lamba et al, 2003) clearance were higher in females for various substrates, although conflicting data have been reported and interindividual differences may prevail (Yang et al, 2013;Tracy et al, 2016). Conflicting results were also obtained for CYP2C9 (Houghton et al, 1975;Rugstad et al, 1986;Karim et al, 1997), CYP2C19 (Richardson et al, 1985;Rugstad et al, 1986;Hooper and Qing, 1990;Laine et al, 2000) and CYP2D6 (Walle et al, 1989;Pritchard et al, 1992;Tamminga et al, 1999;Labbé et al, 2000;Hägg et al, 2001;McCune et al, 2001;Aichhorn et al, 2007) depending on the substrate. Moreover, CYP2C19 and CYP2D6 are highly polymorphic genes, which makes it even more challenging to draw conclusions (Goldstein, 2001;Cascorbi, 2003).…”
Section: Sex-related Differences In Cyp Protein Abundance In the Adult Göttingen Minipigmentioning
confidence: 99%
“…Piroxicam is included in the list of commonly used drugs that bind to site I on albumin (Srinivasan et al 1995); the extent of binding is 99Á3%. Karim et al (1997) investigated the effect of this binding behaviour on the disposition kinetics of piroxicam at steady state and it was shown that HSA binding was not dependent on plasma concentration.…”
mentioning
confidence: 99%